Evaluation of the Thermal Comfort in the Design of the Museum Routes: The Thermal Topology - Selma SARAOUI; Azeddine Belakehal; Abdelghani Attar; Amar Bennadji (Journal of Contemporary Urban Affairs, 2018)
Museums are nowadays among the most popular projects for the public, the concept of thermal comfort in museums is often treated after the realization. Even if in the design, the architect shows a particular intention to work with daylight which is considered for these projects as main, the architect often considers certain elements that have an influence on the energy balance of these projects such as orientation, building materials,....The museum route is the key to the success of any museum project, it is the space of the visitor, the space in which he is invaded by sensations. In this study, we will first evaluate the thermal comfort in the museum as a whole (building) and then through its route. the objective is to guide reflection in the design of the museum towards the route in order to reduce energy consumption. In order to carry out our study, some European museums were analysed by means of simulation, according to the thermal comfort of their designs for the most unfavourable conditions, then by thermal analysis of the museum route according to the segmentation principle using the average radiant temperature. this method allowed us to bring out correspondences between the architectural form and the route. finally, the segmentation method constitutes the basis of a new methodological approach called "thermal topology" based on the discontinuities of the temperatures in the route.